Armillaria desertorum, A new species of Armillaria (Agaricales, Basidiomycota) from Inner Mongolia, China - Hou, Weinan; Zu, Jihong; Bau, Tolgor (Phytotaxa, 2025)
A new species, Armillaria desertorum sp. nov., was discovered in Inner Mongolia using ITS, LSU and tef1-ɑ sequences, combined with morphological and molecular phylogenetic analyses. It is characterized by pileus with sparse yellow-brown scaly scales, stipe base with black thick rhizomorph, growing in the sand around the roots of decaying Caragana korshinskii and Populus euphratica. We provide illustrated descriptions, molecular characterization and its position in the phylogenetic tree.